Mechanistic investigations of phase behavior in Eudragit (R) blends - Menjoge, Anupa R.; Kulkarni, M. G. (International Journal of Pharmaceutics, 2007)
Blends of Eudragit (R) E (EE) and polymeric excipients using thermal analysis and FTIR spectroscopy were examined. The interactions amongst the blend components were quantified in terms of parameters K-1 and K-2 in Schneider equation and were explained on the basis of interactions between the functional groups of the blend constituents investigated by FTIR spectroscopy. EE formed miscible blends with EC and polyelectrolyte complexes increasing in strength in the order: ES < HPMCP < CAP < EL. From the T-g data the weight fraction of EE in the polyelectrolyte complex was determined. The importance of formulating polyelectrolyte complexes in stoichiometric ratios has been highlighted. The duration over which the release can be sustained by polyelectrolyte complexes has been correlated with equilibrium swelling of the polyelectrolyte complex and parameter K, for the first time. This would help in the choice of blend constituents and composition to tailor drug release. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: degree of swelling; Glass transition temperature; miscibility; polyelectrolyte complex; polymer blends; polymer-polymer interactions

Mechanical properties of polypropylene blended with esterified and alkylated lignin - Maldhure, Atul V.; Ekhe, J. D.; Deenadayalan, E. (Journal of Applied Polymer Science, 2012)
Lignin does not show miscibility with commercial polyolefins. Therefore, industrial waste lignin was modified in two different ways and subsequently blended with commercial polypropylene (PP) up to 25 wt %. A Brabender electronic plasticorder was used for melt mixing at 190 degrees C. The influence of different modifications on the mechanical properties and processing stability was studied for both polymer blends. The blends of PP and lignin modified (esterified) with maleic anhydride showed less deterioration in the mechanical properties compared to blends of PP and alkylated lignin with dichloroethane. Intermolecular interactions between the PP matrix and modified lignin were concluded on the basis of indicative values derived from various relevant theoretical models to the experimental data. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: mechanical properties; miscibility; modification; polymer blends